Application of Energy Saving and Environmental Protection Materials in Architectural Design - Zixiang Yan (Advances in Materials Science and Engineering)
With the improvement of the living standards of the Chinese people, the construction of the economic system will change from one that meets the needs of the people to one that is perfect. Under the current environment of building a resource-saving socialist harmonious society, it is very necessary for architectural design practitioners to return to the original architectural design and pay attention to the design and use of building materials during construction. The purpose of this paper is to explore and analyze the application of energy saving and environmentally friendly materials in architectural design. This paper firstly analyzes the building’s energy consumption and building’s energy efficiency. Every major achievement in building energy efficiency will be an important means of mitigating the Earth’s energy. Building energy saving has become a major trend of global development, and then the optimal design of reinforcement selection for reinforced concrete beams based on a multiobjective genetic algorithm is discussed. The area of reinforcement required for the member control section is obtained according to the structural analysis program, the main purpose of reinforcement selection is to select safe, economical, and reasonable reinforcement on the premise of meeting the provisions of the code and the requirements of reinforcement structure. Finally, this paper conducts experimental research on the application of phase change energy storage building material SP28 in building energy conservation. The experimental results in this paper show that when the mass ratio of the phase change energy storage material in the wall is less than 15%, there is no wetting and leakage phenomenon. However, when the mass ratio of the phase change energy storage material contained in the wall is greater than 15%, the phenomenon of wetting and leakage will occur, which will cause greater losses when added to the wall. Therefore, it is not suitable for application and building walls. Regardless of leakage, wetting, or economic considerations, the mass ratio of phase change material of 10% is the most suitable for use in walls. It not only has no wetting and no leakage but also has a good energy storage effect and can effectively adjust the ambient temperature.